HAM DAN POLITIK KRIMINAL PASCA ORDE BARU (KONSTRUKSI PELANGGARAN HAM PADA KASUS PEMBANTAIAN DUKUN SANTET DI KABUPATEN BANYUWANGI TAHUN 1998) - Juang, Rhayi Permata; Erviantono, Tedi; Ali Azhar, Muhammad (Jurnal Nawala Politika, 2016)
ABSTRACT This research is motivated by the case of human rights violations during the massacre witches in Banyuwangi in 1998. The central government that when it is exposed to many issues require a diversion issues in other areas to divert attention began when the reform era turn of the new order of oligarchs capitalist towards a democratic state. Therefore, this study will analyze the motives brutality of human rights violations that led to the massacre of the witches. The purpose of this research that examines how government as the dominant party using a various social control to a group that dominated the society. This study used qualitative methods - descriptive. The subjects were the victims and the community leaders who concern about the problems of this massacre case. By using the theory of hegemony to explore the phenomenon of the role of the state to a case that comes to the human rights violations like this. Namely data collection techniques with direct observation to the test site and the literature to comparison be empirical research results also snowball technique purposive sampling. Based on the analysis of cases of human rights violations during the massacre witches in Banyuwangi 1998 as a whole is a game the government on the transfer issue. Turbulent political force people to accept an issue to distract him from the turmoil in the capital but did not go according to the destination. The lack of public understanding about the violation of Human Rights to make the case - a case that concerned have not or even cannot be resolved properly, including cases of human rights violations in Banyuwangi 1998's .   Keywords: New Order, Human Rights Violations, Hegemony Gramsci